PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA REGU PENJAGAAN DI LEMBAGA PEMASYARAKATAN KELAS II A KEROBOKAN - I Made Bhaskara Jaya Wardana; Mitro Subroto (Jurnal Komunikasi Hukum, 2022)
This research was conducted to determine the influence of leadership style on the motivation of the guard team work in Lembaga Pemasyarakatan Kelas II A Kerobokan. In this study the authors used quantitative research methods with a population of all guarding squads in Lembaga Pemasyarakatan Kelas II A Kerobokan of 58 people. The sampling process in this study uses saturated sample techniques because the entire population in this study is a sample. The results of this study showed that 23.9% of the motivation of the guard squad at Lembaga Pemasyarakatan Kelas II A Kerobokan was influenced by leadership style while the remaining 76.1% was influenced by other models not discussed in this study. This study concluded that leadership style influenced the motivation of the guard team's work at Lembaga Pemasyarakatan Kelas II A Kerobokan.